Connecting the Dots Between Hypercholesterolemia and Alzheimer’s Disease: A Potential Mechanism Based on 27-Hydroxycholesterol - Wu, Mingan; Zhai, Yingying; Liang, Xiaoyi; Chen, Weichun; Lin, Ruiyi; Ma, Linlin; Huang, Yi; Zhao, Di; Liang, Yong; Zhao, Wei; Fang, Jiansong; Fang, Shuhuan; et al. (Frontiers in Neuroscience, 2022)
Alzheimer's disease (AD), the most common cause of dementia, is a complex and multifactorial disease involving genetic and environmental factors, with hypercholesterolemia considered as one of the risk factors. Numerous epidemiological studies have reported a positive association between AD and serum cholesterol levels, and experimental studies also provide evidence that elevated cholesterol levels accelerate AD pathology. However, the underlying mechanism of hypercholesterolemia accelerating AD pathogenesis is not clear. Here, we review the metabolism of cholesterol in the brain and focus on the role of oxysterols, aiming to reveal the link between hypercholesterolemia and AD. 27-hydroxycholesterol (27-OHC) is the major peripheral oxysterol that flows into the brain, and it affects β-amyloid (Aβ) production and elimination as well as influencing other pathogenic mechanisms of AD. Although the potential link between hypercholesterolemia and AD is well established, cholesterol-lowering drugs show mixed results in improving cognitive function. Nevertheless, drugs that target cholesterol exocytosis and conversion show benefits in improving AD pathology. Herbs and natural compounds with cholesterol-lowering properties also have a potential role in ameliorating cognition. Collectively, hypercholesterolemia is a causative risk factor for AD, and 27-OHC is likely a potential mechanism for hypercholesterolemia to promote AD pathology. Drugs that regulate cholesterol metabolism are probably beneficial for AD, but more research is needed to unravel the mechanisms involved in 27-OHC, which may lead to new therapeutic strategies for AD.